Pelaksanaan Program Pembiasaan Pagi Sebagai Upaya Penguatan Pendidikan Karakter Di Sekolah Mts Wachid Hasyim Jagalempeni Wanasari Brebes - Tsaqofatun Najdah; Tia Novifa Aifi; Likhayatun Nufus; Solekhul Amin,M.Pd (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to describe the implementation of the morning habituation program as an effort to strengthen character education at MTs Wachid Hasyim Jagalempeni Wanasari Brebes. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. The primary data source was obtained through interviews with the teacher in charge of the morning habituation program, while secondary data were obtained from school documents. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The validity of the data was tested through source and technique triangulation. The results showed that the morning habituation program was implemented regularly and systematically before the learning process began. The activities included flag ceremonies, Qur'an recitation, Asmaul Husna recitation, reading short surahs, Yasin, and Tahlil. The program contributed to strengthening students' character through continuous habituation activities. Supporting factors included the cooperation of school members and the availability of structured activity schedules, while inhibiting factors included the lack of student awareness and limited parental support. Therefore, the morning habituation program can serve as an effective effort in strengthening character education at school. This is an open-access article under the CC–BY-SA license.